'Kafeteria Sihat' initiative in Malaysian public hospitals: Do customers accept it?. Issue 1 (2nd January 2020) - Abdul Rahman, Abdul Rais; Zahari, Mohd Salehuddin Mohd; Tamby Chik, Chemah
ABSTRACT: Government health agencies throughout the world have implemented the healthy cafeteria initiative at hospitals to cultivate healthy eating practices as an effort to combat the continuously high prevalence of non-communicable diseases (NCD). In Malaysia, this initiative is known as ' Kafeteria Sihat' . This initiative is one of the lifestyle intervention programs for that community under the first National Strategic Plan for Non-Communicable Diseases and later integrated into the third National Plan of Action for Nutrition Malaysia NPANM III. The present study aims to evaluate customers' level of acceptance toward 'Kafeteria Sihat' through a newly developed structured questionnaire with the option of answering 4 additional subjective questions. A better understanding of customers' overall acceptance can potentially indicate how these cafeterias have been performing in terms of customer retention. Eleven public hospitals in Selangor and Putrajaya were visited for survey purposes. The data were analyzed through frequency tests and descriptive statistics. Overall, the findings indicated that the acceptance of customers toward 'Kafeteria Sihat' was at an average level. Generally, continuous effort between the Ministry of Health and cafeteria operators is essential in creating a better awareness of the existence of 'Kafeteria Sihat' as a platform to cultivate healthy eating practices.